Molecular layer-by-layer assembled forward osmosis membranes - Kwon, Soon-Bum; Lee, Jong Suk; Kwon, Soon Jin; Yun, Seong-Taek; Lee, Seockheon; Lee, Jung-Hyun (ELSEVIER SCIENCE BV, 2015)
A recently devised, molecular layer-by-layer (mLbL) approach based on the alternative cross linking of monomers was employed to fabricate high-performance thin film composite (TFC) forward osmosis (FO) membranes with excellent rejection toward monovalent NaCl salt. An ultrathin and highly dense polyamide (PA) selective layer with a precisely controlled structure was created on a tailored porous support via mLbL. The intrinsic separation properties of the rnLbL-assembled TFC membranes were tuned by adjusting the mLbL cycle number to optimize the FO performance. The best FO performance was achieved at 10 rnLbL cycles (mLbL-10), where the permeability and selectivity were properly balanced. Importantly, the mLbL-10 membrane exhibited superior FO performance compared to the commercial HTI FO membranes as well as hand Cast TFC membranes prepared by the conventional interfacial polymerization: the rnLbL-10 membrane showed similar to 3.5 Limes higher wafer flux, similar to 60% lower reverse salt flux and similar to 85% lower specific salt flux compared to the cellulose triacetate HTI membrane, with 0.5 M NaCl draw solution and DI water teed solution in FO mode. The stability and the associated membrane performance of the mLbL-assembled membrane depending on the ionic strength of the environment were explained by the swelling behavior of the polyelectrolyte-assembled interlayer adhered underneath the PA selective layer. (C) 2015 Elsevier By. All rights reserved.
Keywords: THIN-FILM-COMPOSITE; INTERNAL CONCENTRATION POLARIZATION; PRESSURE RETARDED OSMOSIS; POLYELECTROLYTE MULTILAYER MEMBRANES; ENGINEERED OSMOSIS; POWER-GENERATION; HIGH-PERFORMANCE; SUPPORT LAYER; FO MEMBRANES; WATER FLUX